Analysis of the Implementation of PSAK 109 in Enhancing Transparency and Accountability of Zakat Institutions - Ulil Ikhsan S; Yuliana; M Riski Akbar; Azmy Audian Dirgandari; Asri Sundari (Jurnal Akuntansi, 2025)
Zakat is a key instrument in Islamic economics for wealth redistribution, aiming to reduce social inequality and enhance community welfare. Transparent and accountable zakat management is essential for building and maintaining public trust in zakat institutions. Sharia accounting plays a crucial role in systematically recording, measuring, and reporting zakat finances in accordance with Islamic principles, thereby reinforcing transparency and accountability. This study analyzes the role of Sharia accounting in improving transparency and accountability in zakat management, with a focus on the implementation and challenges of PSAK 109. A qualitative descriptive method is employed, using a literature review of scholarly articles on the application of PSAK 109 in BAZNAS and LAZ. Findings reveal that BAZNAS has effectively implemented PSAK 109, supported by strong regulations, strict oversight, and integrated Sharia accounting systems. In contrast, many LAZ face obstacles, including limited human resources, inadequate technological infrastructure, and weak supervision. To address these issues, efforts should focus on regulatory harmonization, capacity building, digitization of accounting systems, and enhanced oversight by the Sharia Supervisory Board (DPS). Strengthening these areas will enable accounting to contribute more significantly to the professionalization of zakat management, ensuring its distribution is more effective and transparent.